Advances in subcutaneous injections: PRECISE II: a study of safety and subject preference for an innovative needle-free injection system. (1st January 2021) - Kelley, E. Lynne; Smith, Richard H.; Corcoran, Gillian; Nygren, Sandra; Jacoski, Mary V.; Fernandes, Andrea
Abstract: Needle-free injection is a desirable goal for many reasons, including reducing pain, anxiety, and eliminating safety risks associated with needle-stick injuries. However, development of a safe, reliable needle-free device optimized for at-home use has been met with many challenges. Portal Instruments Inc. has been developing needle-free medication delivery using a well-designed hand-held device, PRIME, that is safe, intuitive to use, and utilizes advanced electronic control of a focused, high velocity, pressurized liquid injection stream. The PRECISE II human study demonstrated that the PRIME needle-free injection system was safe, well tolerated, and strongly preferred by participants for self-injections over a standard needle and syringe. In addition, the study was able to be completed early for superiority following the success of the pre-defined interim analysis.